Relationship Between Retinal Blood Flow and Renal Function in Patients With Type 2 Diabetes and Chronic Kidney Disease - Nagaoka, Taiji (American Diabetes Association, 2013)
OBJECTIVE: To study the relationship between retinal microcirculation and renal function in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS: Using a laser Doppler velocimetry system, we obtained the retinal blood flow (RBF) values by simultaneously measuring the retinal vessel diameter and blood velocity. To determine if the RBF is affected in the presence of renal dysfunction, we also evaluated the renal function using the estimated glomerular filtration rate calculated by age and serum creatinine level. RESULTS: We recruited 169 eyes of 169 consecutive Japanese patients with type 2 diabetes, no or minimal diabetic retinopathy, and normo/microalbuminuria (mean age ± SD, 59.0 ± 11.1 years). We divided the patients into four groups based on the stage of chronic kidney disease (CKD) (non-CKD, n = 99; CKD stage 1, n = 22; stage 2, n = 27; stage 3, n = 21). We found significant (P = 0.035) decreases in RBF with decreased vessel diameter (P = 0.017) but no difference in blood velocity (P = 0.54) in stage 3 CKD compared with the non-CKD group. Multiple regression analysis showed that the CKD stage was significantly (P = 0.02) and independently associated with decreased RBF. CONCLUSIONS: Our results indicated that the vessel diameter and RBF in the retinal arterioles decrease in patients with type 2 diabetes with stage 3 CKD, suggesting that impaired renal function might be associated with decreased RBF, probably via constriction of the retinal arterioles, in early-phase diabetic retinopathy.